Burnout and job satisfaction among community-based rehabilitation (CBR) workers in Kedah / Noor Ain Paharolrozi and Padma A Rahman - Paharolrozi, Noor Ain; A Rahman, Padma (Faculty of Health Sciences, Universiti Teknologi MARA, 2024)
Burnout and job satisfaction were often associated with among workers in health care including Community-Based Rehabilitation (CBR) workers. This study aims to identify burnout and worker satisfaction working at CBR in Kedah, Malaysia. The workers who have working experience of at least six months in CBR in Kedah and can understand English were eligible to participate in the study. Maslach Burnout Inventory (MBI) and Minnesota Satisfaction Questionnaire (Short version) questionnaires were the main instruments that was used in this study. Kruskal-Wallis statistical analysis and multiple regression analysis were used to answer the objectives. The results showed a low level of burnout in Emotional Exhaustion (EE) and Personal Accomplishment (PA) subscales while the Depersonalization (DP) showed a moderate level of burnout. The job satisfaction level showed the mean score of 65.32 (SD=16.86) which indicated the high job satisfaction level among CBR workers. Other than that, there was a significant relationship between burnout and job satisfaction among CBR workers while there was no correlation between demographic data and job satisfaction. This study could assist occupational therapists in developing plan and organize the most effective strategy of action to increase awareness regarding burnout and job satisfaction.